The Design of a Closed-Loop Piezoelectric Friction–Inertia XY Positioning Platform with a Centimeter Travel Range - Zheng-Rong Guo; Hong-Sheng Tan; Chin-Shun Chang; Ing-Shouh Hwang; En-Te Hwu; Hsien-Shun Liao (Actuators)
Friction–inertia piezoelectric actuators can perform long-range positioning with nanometer resolution. However, friction and inertia are not easy to control and can influence the actuator’s performance. The present study proposes a friction–inertia-type piezoelectric XY positioning platform with a simple structure, which uses magnets to provide stable normal force and friction. Sliders and rails were used to provide long travel ranges of 80 mm and 70 mm in the X and Y directions, respectively. Compact optical encoders were installed on the platform to enhance the positioning accuracy. With a three-phase positioning strategy involving both stepping and closed-loop methods, the system achieved a positioning accuracy of 3 µm (0.03%) and a repeatability of 325 nm (0.0033%) over a 10 mm long travel range. The positioning resolution was 4.7 nm, which was primarily limited by optical encoder noise under the closed-loop control mode. An astigmatic optical profilometer was used for the wide-range and high-resolution surface imaging of the XY positioning platform.